Technology and Servicescape Acceptance Influence on Self-Service Bank - Michael, Andrew Octavianus; Fachira, Ira (Journal of Business and Management, 2020)
Abstract. The world of banking has been shifting, with the current trend causing the shift from conventional banks towards the self-service banks. Banks in Indonesia has started to shift also, with the example of CIMB Niaga with its Digital Lounge as a self-service bank. However, the transition from using the conventional bank services towards the usage of Digital Lounge is still low especially for the category of age older than or equal to 40. This study is determined to find whether technology acceptance and servicescape influencing customers’ intention to use self-service banking, in this case, Digital Lounge. The factors used to depict the relation are adapted from a theoretical framework of a previous research, that are Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment, Information on Self-Service Bank, Security and Privacy, Quality of Internet Connection, with the addition of a variable namely Servicescape. A survey was conducted with 258 respondents that fulfilled the criteria and were analyzed in order to find the factors that affects the intention to use of the self-service bank with Digital Lounge as the example. The proposed model was analyzed using Multilinear Regression and Pearson Correlation Coefficient. Finding showed that only Servicescape that significantly affects and has a positive relation towards the intention to use self-service bank for the customers with the age criteria of 40 and above. The descriptive analysis previously shown that Servicescape holds the highest mean score, while the lowest mean score being the factors of Information on Self-Service Bank. This could describe the factor that is highly considered by the customers and affects the hypothesis acceptance and rejections. It is also found that Servicescape needs to be highlighted by CIMB Niaga in order to raise the number of users for the age of 40 or older.Keywords: Banking, Self Service, Servicescape, Technology